Participación de los jóvenes como candidatos en las elecciones seccionales de la Parroquia Malacatos, Cantón y Provincia de Loja, 2023 - Abad Abrigo, Estefanny Elizabeth (2024)
The study in progress focuses on the participation of young people as candidates in the sectional elections in Malacatos Parish, Canton and Province of Loja in 2023. With an interdisciplinary approach, the research seeks to understand the political and social dynamics surrounding these young candidates. The main objective is to unravel the underlying factors that motivate young people to enter local politics. It examine both the personal motivations and the socio-political impulses that guide them towards this participation. Through interviews, we seek to provide a comprehensive view of their expectations, aspirations and commitments, the specific challenges and opportunities facing these young candidates are addressed. The impact of their presence in local politics and their potential to drive generational changes in political representation are explored. The research seeks to provide essential information to understand the emerging political landscape in Malacatos Parish in 2023. By analyzing the contribution of youth candidates to sectional elections, it will shed light on the evolution of youth participation in local and regional decision-making. Testimonies reveal that the lack of support within the candidacies towards youth negatively impacts their political participation. This highlights the importance of support and recognition to encourage the active involvement of youth in local politics. Several internal and environmental variables, such as restricted community connectedness, lack of higher education, economic constraints, and low media presence, contribute to limited youth participation. One of the notable findings is the widespread perception of a low level of youth participation in the political arena. The interviews provide a unique perspective from the youth involved, highlighting dissatisfaction with the results and lack of accountability among candidates. The youth of show a vehement desire to look out for opportunities and address the basic needs of the parish, reflecting an aspiration for more active and effective political participation.